The development of a simulative hybrid model for optimising the production of a high-carbon ferromanganese furnace. - Sundstrom, Ashley William (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2009.